Management of severe complications in Behçet's disease with TNF inhibitors. (3rd July 2017) - Desbois, A. C.; Vallet, H.; Domont, F.; Comarmond, C.; Cacoub, P.; Saadoun, D.
ABSTRACT: Introduction : The efficacy of anti-TNFα agents has been recently evaluated in many studies in Behçet's disease (BD), particularly in ocular and life-threatening manifestations such as neurological and vascular disease. Areas covered : The following article aims to summarize the currently available efficacy and safety data of anti-TNFα agents in BD. Expert opinion : Most studies have shown dramatic and rapid efficacy with anti-TNFα agents on the main BD-associated issues including posterior uveitis, gastro-intestinal and neurological complications as well as major vessel disease. Experts in the field do recommend the use of anti-TNF agents (either infliximab or adalimumab) as a first-line therapy in severe posterior uveitis in BD and now use anti-TNFα treatment in BD-associated life threatening manifestations. However, data is mainly based on retrospective cohorts or open-label prospective studies. Controlled studies (versus conventional immunosuppressants such as azathioprine and cyclophosphamide) are warranted to properly evaluate their efficacy as first line therapeutic in life-threatening manifestations of BD.